2022
DOI: 10.7575/aiac.ijkss.v.10n.2p.16
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Five-Week Aerobic Interval Training on The Body Composition of Pencak Silat Elite Athletes

Abstract: Background: Background: The direction of coaching is emphasized as a factor affecting the physical conditions of pencak silat martial arts athletes in all categories. One of the physical exercises that affects body composition is aerobic activity. Objective: This study aimed to examine the effects of aerobic interval (AI) training performed for five weeks on the body mass index (BMI), basal heart rate, and the VO2max of elite athletes. Methods: The study used an experimental design involving total sampling. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
5
0
4
Order By: Relevance
“…The other study found that long-distance running training is practical in adapting endurance, body composition, and flexibility (Nikolaidis et al, 2021). Aerobic interval training for five weeks, two times a week, per session was a maximum of 77 minutes improved the physical condition of athletes (Lubis, et al, 2023).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The other study found that long-distance running training is practical in adapting endurance, body composition, and flexibility (Nikolaidis et al, 2021). Aerobic interval training for five weeks, two times a week, per session was a maximum of 77 minutes improved the physical condition of athletes (Lubis, et al, 2023).…”
Section: Discussionmentioning
confidence: 93%
“…Tests related to VO2 max with training variables (training load and speed) and anthropometric variables affecting long-distance race times (Alvero-Cruz et al, 2020). Five-week interval training reduced body weight, body mass index, fat, basal heart rate, and increased VO2 max (Lubis et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Sejak usia mudah dapat lebih mudah dilakukan pembentukan dan sosialisasi. Adanya sosialisasi menjadikan generasi penerus mereka dapat memasyarakatkan olahraga cricket di seluruh Indonesia (Lubis et al, 2021).…”
Section: Pendahuluanunclassified
“…Instrumen yang digunakan dalam penelitian ini merupakan rangkaian tes kondisi fisik yang dilakukan secara berurutan. Menurut (Lubis et al, 2022) tes untuk mengukur profil kondisi fisik dapat dilakukan melalui 1) Tes Index Masa Tubuh; 2) Tes Kemampuan Kecepatan 20 meter; 3) Tes Kemampuan Kelincahan (Lari Bolak-balik); 4) Tes Kemampuan Power Tungkai (Vertical Jump); 5) Tes Kemampuan Kekuatan Otot Perut (Sit Up); 6) Tes Kemampuan Kekuatan Otot Lengan (Push Up); 7) Tes Lari Multitahap (MFT) (Lubis et al, 2022;Lusianti, 2021;Shava et al, 2017). Data nilai yang didapatkan dari pengujian terhadap sampel kemudian dianalisis dengan menggunakan teknik analisis statistik deskriptif yang dilakukan melalui aplikasi SPSS.…”
Section: Metodeunclassified